EFFECT OF COMPETENCE AND COMPENSATION ON EMPLOYEE PERFORMANCE - Sumerli A, Chevy Herli; Deddy Novie Citra Atra,; Yeti, Yeti; Betty Rahayu,; Muhammad Yusuf, (Journal of Innovation Research and Knowledge, 2022)
The purpose of this study to discuss about effect of competence and compensation on employee performance. This type of research is a correlational study. The population in this study are employees of PT Bintang Parabola, amounting to 75 people. In this study the authors used a population of 75 employees at PT Bintang Parabola by calculating the sample size using saturated sampling technique. Methods of data analysis using the t test. The research results show that competence has a significant effect on employee performance at PT Bintang Parabola. Compensation has a significant effect on employee performance at PT. Bintang Parabola.